JOURNALISTIC LANGUAGE AS A FRAMING TOOL: ANALYSIS OF IMMANUEL EBENEZER’S REPORTS ON KOMPAS.COM AND TEMPO.CO - Muhammad Ihlasul Amal; Muh. Medriansyah Putra Kartika; Eka Kurnia Syawaliyah Subagio (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study examines differences in meaning construction within online news reports of the Corruption Eradication Commission (KPK) sting operation against Deputy Minister of Manpower Immanuel Ebenezer in August 2025. The case illustrates how media framing shapes public interpretation of legal and political events. The research focuses on how Kompas.com and Tempo.co framed the incident and how these differences reflect each outlet’s ideological orientation in constructing social reality. Using a qualitative approach and the Pan & Kosicki framing model, which analyzes syntax, script, thematic, and rhetorical structures. This study analyzes 16 news articles published by Kompas.com and Tempo.co between August 21-30, 2025. Articles were selected based on their relevance and representativeness of the issue’s framing patterns. The findings indicate that Kompas.com adopts a moral-political frame emphasizing legitimacy and the ethical crisis of power, while Tempo.co employs a legal-formal frame highlighting rationality and institutional accountability. These framing contrasts reveal distinct orientations in defining the meaning of corruption and authority. The study concludes that media framing operates as an ideological mechanism that not only reports events but also constructs interpretive frameworks guiding public understanding of the relationship between law, politics, and morality in Indonesia’s public discourse.